Potential of Palm Kernel Alkanolamide Surfactant for Enhancing Oil Recovery from Sandstone Reservoir Rocks: DOI: 10.32526/ennrj.18.4.2020.32 - Traiwiriyawong , Parichat; Kungsanant, Suratsawadee (Environment and Natural Resources Journal, 2020)
The interest in using benign surfactants has been steadily increasing in the context of enhanced oil recovery (EOR). Palm kernel alkanolamide surfactant (PKA), a nonionic surfactant synthesized from palm kernel oil, was preliminarily assessed for EOR from sandstone reservoir rocks. The performance factors determined were silica adsorption for surfactant loss and crude oil solubilization for oil solubilizing efficiency. The performance of PKA was compared to two commercial ionic surfactants, SDS (anionic surfactant) and CTAB (cationic surfactant). The results show that PKA was less absorbed on silica than CTAB or SDS. The adsorption kinetics were well fit with a pseudo-second order model for all three surfactants. The adsorption equilibrium data for CTAB and PKA were fitted with Langmuir isotherm, while for SDS Freundlich isotherm fit well, indicating multilayer SDS adsorption on silica surfaces. The adsorption of PKA was not significantly affected by added salt or increased temperature. In addition, the solubilization equilibrium constant (Ks) had the rank order PKA > CTAB > SDS, and proportionally increased with added salt. PKA performance was also compared to two commercial nonionic surfactants, Tergitol 15-S-9 and Tergitol TMN-6, and the results indicate that PKA was the least adsorbed, and had the highest Ks among the tested nonionic surfactants.